If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = x + -6 Reorder the terms: -3 + 4x = x + -6 Reorder the terms: -3 + 4x = -6 + x Solving -3 + 4x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 4x + -1x = -6 + x + -1x Combine like terms: 4x + -1x = 3x -3 + 3x = -6 + x + -1x Combine like terms: x + -1x = 0 -3 + 3x = -6 + 0 -3 + 3x = -6 Add '3' to each side of the equation. -3 + 3 + 3x = -6 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -6 + 3 3x = -6 + 3 Combine like terms: -6 + 3 = -3 3x = -3 Divide each side by '3'. x = -1 Simplifying x = -1
| 0=48+32t-16t^2 | | -2+8(x-1)=12x+4-4x | | 5m-4n=10 | | 3x(x+2)=2 | | 10m-9n=15 | | 3x^2=2-4x | | 4x+4=7x-8 | | 8n-25=3n+5 | | 10-20=6x+4 | | 11y=3y+4 | | 32=16x-2x^2 | | 6=9y-3y-6 | | 6x+36=-1 | | -x+10=3x-14 | | 3y+4=11y | | 14(p^2-1)=45p | | 6=-9+c | | 5p+2=17 | | -3.4x+30.535=-3(-1.9+7.23x)-2.6 | | -4x+5=7-5x | | 25x^2+49=70x | | 8j-19+9j=15 | | y=4+8 | | 7.5(n-0.3)=-3.051-0.51n | | 86=-10-8a | | 7x+7=-4x-70 | | (6n)-2=22 | | -27.73+4.5r=-2(7.1+3.9r) | | -6.7m+32.671=-3.3(3.7m-5.1)+0.4m | | (1+(2-3)-(4+2))*2= | | -3(4b-10)=(-24d+60) | | 6n-(2)=22 |